A simple dot blot assay to measure hygromycin B phosphotransferase activity in whole cell extracts of Neurospora crassa - Michael Freitag; Matthew S. Sachs (Fungal Genetics Reports, 1995)
Hygromycin B (Hyg) is an aminocyclitol antibiotic with broad spectrum activity against prokaryotes and eukaryotes (Pettinger et al. 1953 Antibiot. Chemother. 3:1268- 1278). Hyg inhibits protein synthesis by blocking ribosomal translocation; it prevents polypeptide elongation by interfering with aminoacyl tRNA recognition and ribosomal A-site occupation (Cabanas et al. 1978 Euro. J. Biochem. 87:21-27, Hausner et al. 1988 J. Biol. Chem. 263:13103-13111). Hyg can lead to misreading during translation in vitro (Davies and Davies 1968 J. Biol. Chem. 243:3312-3316, Gonzales et al. 1978 Biochim. Biophys. Acta 521:459-469, Singh et al. 1979 Nature 277:146-148); however, this effect was not duplicated in vivo (Bakker 1992 J. Gen. Microbiol. 138:563-569).